1998
DOI: 10.1002/1529-0131(199801)41:1<110::aid-art14>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of stromelysin 1-deficient mice to collagen-induced arthritis and cartilage destruction

Abstract: Disruption of the SLN1 gene neither prevents nor reduces the cartilage destruction associated with CIA. Moreover, SLN1 depletion does not prevent the cleavage of the aggrecan Asn341-Phe342 bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(97 citation statements)
references
References 62 publications
(21 reference statements)
1
91
1
2
Order By: Relevance
“…In both investigations, MMP-3 (stromelysin 1) was, by far, the most abundantly expressed protease, and MMP-3 was significantly down-regulated in OA cartilage. These data suggest that MMP-3 does not represent the driving force in final matrix degradation in OA cartilage, which is further documented by the fact that MMP-3 knockout mice and their wild-type littermates are equally susceptible to cartilage destruction (51). Rather, MMP-3 appears to be a major contributor to physiologic matrix turnover in normal articular cartilage (52,53).…”
Section: Discussionmentioning
confidence: 93%
“…In both investigations, MMP-3 (stromelysin 1) was, by far, the most abundantly expressed protease, and MMP-3 was significantly down-regulated in OA cartilage. These data suggest that MMP-3 does not represent the driving force in final matrix degradation in OA cartilage, which is further documented by the fact that MMP-3 knockout mice and their wild-type littermates are equally susceptible to cartilage destruction (51). Rather, MMP-3 appears to be a major contributor to physiologic matrix turnover in normal articular cartilage (52,53).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, patients with high serum/plasma levels of MMP-3/MMP-9 might be susceptible to rapid destruction of the large joints. However, studies in MMP-3-deficient mice revealed that collagen-induced arthritis, in which MMP-3 messenger RNA is highly induced, was not prevented (6).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are thought to play an important role in the matrix degradation of OA (4)(5)(6). Although the mechanism of the rapid destruction of the hip joint in this subgroup of OA is still unknown, previous biochemical studies suggest that fibroblasts from the synovium and subchondral cysts may secrete much higher levels of MMPs than are typically secreted in ordinary OA (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-3-deficient mice were generated by homologous recombination as described previously and maintained on a 129/SvEv background. [16][17][18] Experimental protocols were approved by the Institutional Animal Care and Use Committee of the University of Yamanashi (No 19-105), Japan.…”
Section: Micementioning
confidence: 99%